2016
DOI: 10.1038/cddis.2016.166
|View full text |Cite
|
Sign up to set email alerts
|

BDNF pro-peptide regulates dendritic spines via caspase-3

Abstract: The precursor of brain-derived neurotrophic factor (BDNF) (proBDNF) is enzymatically cleaved, by either intracellular (furin/PC1) or extracellular proteases (tPA/plasmin/MMP), to generate mature BDNF (mBDNF) and its pro-peptide (BDNF pro-peptide). Little is known about the function of BDNF pro-peptide. We have developed an antibody that specifically detects cleaved BDNF pro-peptide, but not proBDNF or mBDNF. Neuronal depolarization elicited a marked increase in extracellular BDNF pro-peptide, suggesting activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 42 publications
2
58
0
Order By: Relevance
“…However, recent studies have reported that exposure of pro-BDNF to hippocampal neurons in culture dramatically reduces dendritic spine density. The cellular mechanism was reported as pro-BDNF increasing the number of “elongated” mitochondria and cytosolic cytochrome C, suggesting involvement of the mitochondrial caspase-3 pathway [27]. In the “learned helplessness” model of depression, the pro-BDNF level is increased while mBDNF declines in the prefrontal cortex; this is reversed by the BDNF TrkB receptor antagonist [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have reported that exposure of pro-BDNF to hippocampal neurons in culture dramatically reduces dendritic spine density. The cellular mechanism was reported as pro-BDNF increasing the number of “elongated” mitochondria and cytosolic cytochrome C, suggesting involvement of the mitochondrial caspase-3 pathway [27]. In the “learned helplessness” model of depression, the pro-BDNF level is increased while mBDNF declines in the prefrontal cortex; this is reversed by the BDNF TrkB receptor antagonist [28].…”
Section: Discussionmentioning
confidence: 99%
“…The third report (3) found that the Val‐pBDNF reduces dendritic spine density in hippocampal neurons (Guo et al . ). The key findings of these three publications are analyzed below and summarized in Table .…”
Section: A Prodomain As An Independent Signaling Ligand: Pbdnfmentioning
confidence: 97%
“…f) (Guo et al . ). Notably, this effect was evident 24 h after the administration of the ligand, but not earlier.…”
Section: A Prodomain As An Independent Signaling Ligand: Pbdnfmentioning
confidence: 97%
See 2 more Smart Citations